Metal oxide nanowire chemical sensors: innovation and quality of life. Issue 10 (December 2016) - Comini, Elisabetta
Abstract : Metal oxides are emerging as important active materials for applications such as sensors. Recent advances in the preparation of metal oxide materials offer unique possibilities for their integration into devices with new capabilities, for example, wearable/flexible devices, smart textiles for well-being and health monitoring in everyday life, or with innovative sensing architectures such as work function, surface ionization, magnetic, self-heating, and Schottky-based devices. This review presents the author's opinion on innovations and challenges in the field of metal oxide nanowire chemical sensors.